Regulatory disparities and operational challenges in ASEAN rail transit: Insights from Thailand and Lao PDR - Weeraphan, Paramaporn; Seehawattana, Acharaporn; Jongudomkarn, Peachaya (Edelweiss Applied Science and Technology, 2025)
This study examines the laws and customs procedures that govern transit rail transport between Thailand and Lao PDR. The aim is to identify inefficiencies to formulate an operational framework conducive to cross-border logistics. Although Thailand and Lao PDR are parties to regional agreements such as the ASEAN (Association of Southeast Asian Nations) Single Window (ASW), disparities remain due to each country's unique political priorities, trade practices, and border control mechanisms. Drawing on documentary research and field investigations conducted at key rail logistics points, this study identifies procedural redundancies, digital integration gaps, and documentation and border handling inconsistencies. The research uses comparative analysis to evaluate existing practices against successful models like the One-Stop Border Inspection (OSBI) system. Stakeholder interviews and observational data further inform the development of a harmonized inspection framework tailored to the Thai-Lao context. Current rail transit operations are constrained by fragmented legal mandates and technological incompatibility, causing operational delays, increased costs, and additional complexities. The proposed joint customs inspection model, grounded in regulatory harmonization, sharing digital infrastructure, and coordinated border management, can improve procedural efficiency and regional connectivity. This study presents a policy-oriented solution to streamline rail customs procedures between Thailand and Lao PDR. The proposed solution provides a framework to guide regulatory alignment that purports to facilitate the removal of legal and logistical barriers to transit trade—the framework also overtures the digital integration of customs administrations. The findings offer actionable insights for policymakers seeking to advance ASEAN rail transit integration. The study demonstrates that its findings provide implementable insights for policymakers pursuing ASEAN rail transit integration. It emphasizes the requisite conditions (i.e., bilateral policy coordination and system-level interoperability) that allow logistical advantages from cross-border railways to coexist with national sovereignty.